PERANCANGAN MESIN PENGGILING SEKAM PADI - Sukma, Hendri; Kamarullah, Muhammad Rifky (Jurnal Vokasi Indonesia, 2021)
The design of the rice husk grinding machine aims to convert rice husk waste into more useful products. The results of the mill in the form of powder can be used as biomass, charcoal briquettes, animal feed, and others so that rice husk waste can be processed and does not pollute the ecosystem in its environment. The design method in the rice husk grinding machine uses the Pahl and Beitz method which consists of several design and research phases including, functional structure, variant concept creation, value weighting from the questionnaire results and the final result obtained is a technical drawing of the selected variant. The design of the rice husk grinding machine uses an AC (Alternating Current) electric motor with 2 hp (horsepower) with a rotation of 1400 RPM (Radian Per Minute). The milling system of the machine uses a disk mill type knife, with a total of 4 rotational blades and 32 static blades, then the output of rice husks that have been milled with a knife filtered by a mesh sieve no. 20 or 0.8 mm. The final result of this machine mill is in the form of filtered rice husk powder, which is then processed into more useful products.